Men of ideas : some creators of contemporary philosophy - Magee, Bryan (New York : Oxford university press, 1978)
Fifteen dialogues drawn from the highly acclaimed BBC series review the tenets and theories of moral philosophy, political philosophy, the philosophy of language and the philosophy of science.
Includes index.
Keywords: Philosophers -- Modern -- Interviews; Philosophy -- Modern -- 20th century